Edward the Confessor : the man and the legend - Mortimer, Richard, 1949- (Boydell Press, 2009)
The millennium of Edward the Confessor's birth presents an appropriate occasion for a full-scale, up-to-date reassessment of his life, reign and cult, a reappraisal which is provided in the essays here. After an introduction to the many views of Edward's.